2013
DOI: 10.1051/0004-6361/201321945
|View full text |Cite
|
Sign up to set email alerts
|

Herschel/PACS spectroscopy of trace gases of the stratosphere of Titan

Abstract: Aims. We investigate the composition of Titan's stratosphere from new medium-resolution far-infrared observations performed with the full range of Herschel's Photodetector Array Camera and Spectrometer (PACS) (51-220 μm at a resolution λ/Δλ ranging from 950 to 5500 depending on wavelength and grating order). Methods. Using PACS, we obtained the spectral emission of several features of the Titan's stratosphere. We used a line-by-line radiative transfer code and the least-squares fitting technique to infer the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…We calculated collisionally-induced absorption parameters for N 2 , CH 4 , and H 2 pairs from the works of Borysow and Frommhold (1986a;1986b;1986c;1987), Borysow (1991), and Borysow and Tang (1993). We then initialized models of Titan's atmosphere using N 2 and CH 4 vertical profiles from Niemann et al (2010) and Teanby et al (2013), with a constant CO abundance of 49.6 ppm as found by Serigano et al (2016), which is in agreement with previous CO measurements (de Kok et al 2007;Teanby et al 2010b;Gurwell et al 2011;de Bergh et al 2012;Teanby et al 2013;Rengel et al 2014). Assuming the CO abundance profile is constant due to its long photochemical lifetime allows us to fit spectra by only varying vertical temperature profiles, as emission lines of CO are significantly pressure-broadened in Titan's atmosphere and thus enable temperature retrievals from a wide range of altitudes.…”
Section: Spectral Modeling and Resultssupporting
confidence: 77%
“…We calculated collisionally-induced absorption parameters for N 2 , CH 4 , and H 2 pairs from the works of Borysow and Frommhold (1986a;1986b;1986c;1987), Borysow (1991), and Borysow and Tang (1993). We then initialized models of Titan's atmosphere using N 2 and CH 4 vertical profiles from Niemann et al (2010) and Teanby et al (2013), with a constant CO abundance of 49.6 ppm as found by Serigano et al (2016), which is in agreement with previous CO measurements (de Kok et al 2007;Teanby et al 2010b;Gurwell et al 2011;de Bergh et al 2012;Teanby et al 2013;Rengel et al 2014). Assuming the CO abundance profile is constant due to its long photochemical lifetime allows us to fit spectra by only varying vertical temperature profiles, as emission lines of CO are significantly pressure-broadened in Titan's atmosphere and thus enable temperature retrievals from a wide range of altitudes.…”
Section: Spectral Modeling and Resultssupporting
confidence: 77%
“…The average stratospheric value from GCMS is 1.48 ± 0.09%, which is consistent with initial determinations of the stratospheric methane mixing ratio from the Composite Infrared Spectrometer (CIRS) (1.6 ± 0.5% [ Flasar et al , ]) and DISR [ Bézard , ]. However, measurements from the Cassini Visible and Infrared Mapping Spectrometer (VIMS) (1.28 ± 0.06% [ Maltagliati et al , ]), Herschel SPIRE (1.33 ± 0.07% [ Courtin et al , ]), and Herschel PACS (1.29 ± 0.03% [ Rengel et al , ]) find lower stratospheric values. Recent analyses of Cassini CIRS measurements find variation with latitude from 1% at low latitudes to 1.5% at polar latitudes, indicating that the methane mixing ratio in the stratosphere may be more complicated than previously thought [ Lellouch et al , ].…”
Section: Titan's Atmospheric Structure and Compositionsupporting
confidence: 82%
“…Hörst et al [2008] demonstrated that this previously unknown source explains the presence of oxygen-bearing species, and the plumes of Enceladus are likely responsible for the fourth most abundant molecule in Titan's atmosphere (CO), revealing a unique connection between two very different moons in the Saturnian system. Subsequent measurements of H 2 O [Cottini et al, 2012;Moreno et al, 2012;Rengel et al, 2014] have shown some disagreement with their model, and further refinement may be necessary [Krasnopolsky, 2012;Moreno et al, 2012;Dobrijevic et al, 2014;Lara et al, 2014]. The oxygen-bearing species are unique in Titan's atmosphere, because they include photochemically produced molecules that span atmospheric lifetimes of ∼10 years (H 2 O) to ∼1 Gyr (CO) [Hörst et al, 2008]; as such they provide an important opportunity to test photochemical models of Titan's atmosphere.…”
Section: Atmospheric Chemistrymentioning
confidence: 99%
“…Solid line: nominal (OH flux of 10 7 cm −2 s −1 ); dash-dot and long dash -double short dash line: eddy mixing coefficient K 0 = 10 2 and 10 3 cm −2 , respectively, section 2.4; long dashed dotted line: CO fixed, no external flux. The data shown for CO is from CIRS (De Kok et al, 2007;Teanby et al, 2010), VIMS (Baines et al, 2006;Bellucci et al, 2009;Fabiano et al, 2017), Herschel SPIRE (Courtin et al, 2011), Herschel PACS (Rengel et al, 2014); for H 2 O is from ISO (Coustenis et al, 1998) (two circles at 400 km, one with small error bar is assuming constant profile, the one with large error bars is the scaled Lara profile), CIRS (Cottini et al, 2012) (lower 3 circles), INMS (Cui et al, 2009b) (upper limits are average of all the flybys, circles are individual detections from single flybys), Herschel (Moreno et al, 2012) (green line, SA profile); for CO 2 is from CIRS (Vinatier et al, 2010), INMS (Cui et al, 2009b); for H 2 CO is from CIRS (Nixon et al, 2010) Early investigations about external sources of oxygen suggested that CO 2 3658 could be produced through a chemical reaction scheme that begins with an 3659 influx of H 2 O into the upper atmosphere from micrometeorite ablation (Lara 3660 et al, 1996;Toublanc et al, 1995;Yung et al, 1984). However, these models 3661 had some difficulty in reproducing the abundance of all three observed species 3662 and a different approach for the origin of O on Titan was needed.…”
Section: Reactionmentioning
confidence: 99%
“…Figure 59: Calculated and observed mole fractions of CO (upper left panel), H 2 O (upper right panel), CO 2 (lower left panel) and other minor oxygen-bearing species (lower right panel).Solid line: nominal (OH flux of 10 7 cm −2 s −1 ); dash-dot and long dash -double short dash line: eddy mixing coefficient K 0 = 10 2 and 10 3 cm −2 , respectively, section 2.4; long dashed dotted line: CO fixed, no external flux. The data shown for CO is from CIRS(De Kok et al, 2007;Teanby et al, 2010), VIMS(Baines et al, 2006;Bellucci et al, 2009;Fabiano et al, 2017), Herschel SPIRE(Courtin et al, 2011), Herschel PACS(Rengel et al, 2014); for H 2 O is from ISO(Coustenis et al, 1998) (two circles at 400 km, one with small error bar is assuming constant profile, the one with large error bars is the scaled Lara profile), CIRS(Cottini et al, 2012) (lower 3 circles), INMS(Cui et al, 2009b) (upper limits are average of all the flybys, circles are individual detections from single flybys), Herschel(Moreno et al, 2012) (green line, SA profile); for CO 2 is from CIRS(Vinatier et al, 2010), INMS(Cui et al, 2009b); for H 2 CO is from CIRS(Nixon et al, 2010).…”
mentioning
confidence: 99%